Digital Health Transformation and Medical Ethics Challenges: A Global Literature Review - Riska Suryani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital health transformation is rapidly reshaping healthcare delivery worldwide, yet its ethical implications remain unevenly conceptualized across disciplines and governance contexts. This study conducts a global integrative literature review to examine how digital technologies—such as artificial intelligence, telemedicine, and health data infrastructures—reconfigure clinical authority, data governance, and moral legitimacy within healthcare systems. Drawing on interdisciplinary sources indexed in major academic databases, the analysis employs qualitative thematic synthesis to identify recurring ethical tensions and conceptual gaps in contemporary scholarship. The findings indicate that digital health systems redistribute decision-making authority across technological and institutional actors, complicating accountability structures and challenging established models of informed consent and professional responsibility. Ethical risks are most pronounced in areas involving opaque algorithmic processes, large-scale data integration, and unequal digital access, all of which influence public trust and healthcare equity. The review further demonstrates that legitimacy in digital health depends on the interaction between inclusive access, transparent governance, and ethical leadership within healthcare organizations. This study contributes a conceptual framework for understanding digital health ethics as a structural governance issue rather than a collection of isolated dilemmas. The findings provide a foundation for future empirical research and policy design aimed at aligning technological innovation with ethically resilient healthcare systems.